Microstructure studies of bio-water-based coated material for metal exposed in various corrosion environment / Najmiddin Yaakob …[et al.] - Yaakob, Najmiddin; Jai, Junaidah; Musa, Mohibah; Idris, Juferi (2014)
The basic formulation of paint consists of a pigment, binder, solvent and additives. Nowadays, all of the components in paint are made from hazardous chemicals which are harmful to the environment. One of the most important aspects in paint formulation is solvent. Solvent is used to carry the solid components of paint allowing consistency of application by brush, roller, and spray or dipping. The choice of solvent also affects the flow of the paint after it has been applied so that the film develops the correct surface appearance. The paint film wets the substrate to which it has been applied thus maximizing adhesion to the surface. These commonly used solvent are organic chemicals which are harmful to the environment and thus leading to the problem in the application of the paint due to the hazardous constituents. Organic solvent based paints are still a serious problem for painters in the construction sector and that there are no general indications, that the problems are going to be solved. On top of this, it showed that painters are at risks for heavily exposure to organic solvents, for instance floor treatment and painting steel constructions. The bio-water based coated material is based from palm oil methyl ester as the solvent. Palm oil methyl ester is environmental friendly and does not contain any volatile organic compounds which are harmful to the environment since it is made of 100% vegetable origin.. It is also an odorless solvent. The formulation of the bio-water-based consists of a pigment, binder, additives and palm oil methyl ester. The formulation of the bio-water-based coating material for metal will be optimized by testing on the adhesion and corrosion test in various corrosive environments. Due to this matter, micro structure studies of the bio-water-based coated material for metal exposed in various corrosive environments will be conducted.